Intelligence science and big data engineering : visual data engineering : 9th International Conference, IScIDE 2019, Nanjing, China, October 17-20, 2019, Proceedings.: visual data engineering : 9th International Conference, IScIDE 2019, Nanjing, China, October 17-20, 2019, Proceedings. Part I ([2019]) - Unknown
No abstract available